Status of the Warka Expedition - North, R.
The Name Uruk/Erech — The Equation Uruk = Warka — History of the German Excavation — Warka’s Geographical Position — The É-Anna Ziggurat — É-Anna Ziggurat After Ur-Nammu — The É-Anna Enclosure — Mosaic, Writing, and Glyptic — É-Anna East — É-Anna Northwest — Rêš, the Anu-Sanctuary — “White Temple” Anu-ziggurat — Dating Trench — The South Building, Irigal — Parthian Remains — The Outer Periphery of Warka — Summary of Excavation-Phases — Chronological Survey.